Invisibilisation de la pénibilité au travail, mixité et rapports de genre - Camille Noûs (La Nouvelle Revue du Travail)
The article focuses on the sexualised modalities involved in the recognition of strenuous work, drawing from a comparative investigation of two socio-professional categories working for a transport company (drivers and commercial staff members). It shows that the invisibilisation of actions that are damaging to female workers' health largely depends on mechanisms relating to the gender-based distribution of labour as well as traditionaall social representations of strenuous work, often revolving around an approach that associates work considered strenuous solely with the kinds of activities that men undertake in particular technical/industrial settings